Hair and Blood Trace Elements (Cadmium, Zinc, Chrome, Lead, Iron and Copper) Biomonitoring in the Athletic Horse: The Potential Role of Haematological Parameters as Biomarkers - Aragona, Francesca; Giannetto, Claudia; Piccione, Giuseppe; Licata, Patrizia; Deniz, Ömer; Fazio, Francesco (MDPI AG, 2024)
The aim of the present study was the evaluation of the bioaccumulation of cadmium (Cd), Zinc (Zn), Chrome (Cr), Lead (Pb), Iron (Fe) and Copper (Cu), in the blood, serum, tail and mane of horses from the industrialized area of Milazzo (Messina, Sicily), to understand the relationships between haematological parameters: Red Blood Cells (RBCs), White Blood Cells (WBCs), Haemoglobin (Hb), Haematocrit (Hct), Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH), Mean Corpuscular Haemoglobin Concentration (MCHC), Platelets (PLTs) and the concentrations of trace elements. Blood and hair samples from 20 healthy Italian Saddle horses and water, hay and concentrates samples were obtained to determine the haemogram and mineral concentration using a Thermo Scientific iCAP-Q ICP-MS spectrometer. Descriptive analysis showed a higher concentration of Zn, Cr, Pb, Fe, and Cu in the blood and a higher concentration of Cd in the tail than other substrates. A positive correlation was found for Cr (p < 0.0001) and Zn (p < 0.01) between blood and serum substrates, for Zn (p < 0.001) between mane and tail and for Pb (p < 0.01) between blood and mane, while a negative correlation was observed for Cr (p < 0.01) between blood and tail. Results showed a close relationship between the bioaccumulation of certain trace elements in biological substrates and haematological parameters, which represent useful biomarkers suggesting further studies, given the role of haematological parameters in athletic horses.
Keywords: One Health, blood biomarkers, equine, pollution, trace elements; Veterinary medicine; trace elements; blood biomarkers; Article; QL1-991; SF600-1100; pollution; One Health; Zoology; equine